2023
DOI: 10.1088/1402-4896/acd0df
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-independent high contrast grating 1300 nm dot-in-a-well InAs quantum-dot VCSEL

Abstract: High contrast grating (HCG) 1300 nm InAs/GaAs quantum dot (QD) vertical-cavity surface-emitting laser (VCSEL) has been introduced in this manuscript and the impact of device structure on the self-heating effect and device temperature has been investigated. A self-consistent model that couples the opto-electro-thermal model of the device to the optical gain model is used to calculate optical gain. Simulated results indicate that the proposed structure significantly lowers the hole-burning effect due to a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…It has been demonstrated that the threshold current density of per QD layer as low as 12.5A cm −2 [26], and the lasing temperature reached up to 220 °C [27]. In addition, QD materials emerges to be potentially better gain medium because QD lasers also have excellent properties of lower reflection sensitivity, wider gain bandwidth, and nearly zero linewidth enhancement factor [28][29][30]. The above advantages make QD lasers a particularly attractive light source in the fields such as high-performance data centers and hyperscale computing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the threshold current density of per QD layer as low as 12.5A cm −2 [26], and the lasing temperature reached up to 220 °C [27]. In addition, QD materials emerges to be potentially better gain medium because QD lasers also have excellent properties of lower reflection sensitivity, wider gain bandwidth, and nearly zero linewidth enhancement factor [28][29][30]. The above advantages make QD lasers a particularly attractive light source in the fields such as high-performance data centers and hyperscale computing.…”
Section: Introductionmentioning
confidence: 99%